2022
DOI: 10.1029/2021wr031860
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic Sensitivities and ENSO Variability Across Hydrological Regimes in Central Chile (28°–41°S)

Abstract: The El Niño-Southern Oscillation (ENSO) is the main driver of interannual climate variability globally, manifesting as pseudo-oscillatory oceanic/atmospheric anomaly patterns in the tropical Pacific (e.g., Grothe et al., 2019;Timmermann et al., 2018), and affecting the climate of vast regions, notably across the Pacific Rim. In this region, ENSO exhibits a well-known average pattern of sea surface temperature (SST) and other variables, but also an important degree of heterogeneity across episodes. The phases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 85 publications
(131 reference statements)
1
1
0
Order By: Relevance
“…This aligns with earlier findings of an increase in storm duration during El Niño, irrespective of frequency, as documented by Hernández et al. (2022).…”
Section: Discussionsupporting
confidence: 93%
“…This aligns with earlier findings of an increase in storm duration during El Niño, irrespective of frequency, as documented by Hernández et al. (2022).…”
Section: Discussionsupporting
confidence: 93%
“…Different from satellitebased climate products, ERA5-Land derives from data assimilation algorithms combining forecasts with available observations to estimate different climatic variables (Muñoz-Sabater, 2019). Previous studies have indicated that the gridded ERA5-Land reanalysis data set has better performance than satellite-based precipitation products Water Resources Research 10.1029/2024WR037339 HOU AND WEI in comparison with in situ data and representation of precipitation and evapotranspiration (ET) seasonality (Hernandez et al, 2022;Jiang et al, 2021;Tarek et al, 2020;Teo et al, 2022). Watershed-scale data were summarized as the average value of all grids based on watershed boundaries.…”
Section: Datamentioning
confidence: 99%